Orbital plasmablastic lymphoma. Issue 1 (24th November 2017) - Bloch, Edward; Robinson, Fiona
Key Clinical Message: Plasmablastic lymphoma is an unusual and aggressive form of diffuse large B‐cell lymphoma, which arises more commonly within the oronasal mucosa. It should be considered as a differential diagnosis for rapidly growing periorbital lesions, particularly in the context of HIV positivity. Abstract : Plasmablastic lymphoma is an unusual and aggressive form of diffuse large B‐cell lymphoma, which arises more commonly within the oronasal mucosa. It should be considered as a differential diagnosis for rapidly growing periorbital lesions, particularly in the context of HIV positivity.